Canadian Universities in the Pandemic: Differing Policy Responses to International and Domestic Student Financial Needs - Kirby, Dale (Journal of International Students, 2023)
The COVID-19 pandemic had a significant impact on university enrollments around the world and caused significant challenges for students. This study examined how Canadian universities responded to the financial impacts of the pandemic on international and domestic students and how these responses differed. This work involved the identification and collection of public statements issued by selected Canadian universities during the first two years of the pandemic. This consisted of about 14,000 items posted on university public websites. Under the broad framework of the ecological theory of inclusion, an emergent theme content analysis was used to examine and organize data. This analysis confirmed that there was far less financial assistance provided to international students, and the amount of assistance provided to them was significantly disproportionate to the overall revenues generated by their enrollment at Canadian institutions.